2016
DOI: 10.1111/jnc.13905
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional brain alterations in a murine model of Angiotensin II‐induced hypertension

Abstract: Hypertension is a main risk factor for the development of cerebral small vessel disease (cSVD) - a major contributor to stroke and the most common cause of vascular dementia. Despite the increasing socioeconomic importance arising from cSVD, currently only a few specific treatment strategies with proven efficacy are known. Fundamental to the lack of specific treatments is poor understanding of the disease pathogenesis and a lack of appropriate animal models resembling all symptoms of the human disease. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 63 publications
(168 reference statements)
6
48
0
Order By: Relevance
“…Indeed, there is evidence that circulating leucocytes can infiltrate the CNS. In one study, Ang II-induced hypertension resulted in the accumulation of CD3 + T cells into the cerebral artery wall, suggesting that the vasculature was deleteriously affected (Meissner et al 2017). A more conclusive study showed that spontaneously hypertensive rats with reconstituted bone marrow from normotensive Wistar-Kyoto rats had decreased blood pressure and inflammation (Santisteban et al 2015).…”
Section: Blood-brain Barrier Disruption In Hypertensionmentioning
confidence: 99%
“…Indeed, there is evidence that circulating leucocytes can infiltrate the CNS. In one study, Ang II-induced hypertension resulted in the accumulation of CD3 + T cells into the cerebral artery wall, suggesting that the vasculature was deleteriously affected (Meissner et al 2017). A more conclusive study showed that spontaneously hypertensive rats with reconstituted bone marrow from normotensive Wistar-Kyoto rats had decreased blood pressure and inflammation (Santisteban et al 2015).…”
Section: Blood-brain Barrier Disruption In Hypertensionmentioning
confidence: 99%
“…The use of Angiotensin II (Ang II) infusion has been previously associated with hypertension-induced cerebrovascular dysfunction including increased BBB permeability and neuroinflammation [32][33][34]. We have also shown earlier the presence of activated microglia in association with BBB leakages and short-term memory impairment in a prolonged Ang II infusion (12 weeks) model [35].…”
Section: Introductionmentioning
confidence: 71%
“…An impaired BBB permeability induced by chronic hypertension is associated with microglia activation and short-term memory impairment [32][33][34][35]. In the present study we aimed to determine the contribution of microglia cells to hypertension-induced cognitive impairment using a pharmacological depletion approach.…”
Section: Discussionmentioning
confidence: 98%
“…However, there is no reliable treatment for CSVD . CSVD is characterized by white matter hyperintensities, cognitive impairment, cerebral microbleeds, and cerebrovascular injury in patients . BBB leakage is considered to be the initiating factor of CSVD and is related to the severity of the disease …”
Section: Introductionmentioning
confidence: 99%
“…3,4 CSVD is characterized by white matter hyperintensities, cognitive impairment, cerebral microbleeds, and cerebrovascular injury in patients. 1,5,6 BBB leakage is considered to be the initiating factor of CSVD and is related to the severity of the disease. 7 The blood-brain barrier (BBB) is formed by the endothelium, astroglia, pericytes, and basal lamina.…”
Section: Introductionmentioning
confidence: 99%